Synthesis of o-methyl trifluoromethyl sulfide substituted benzophenones via 1,2-difunctionalization of aryne by insertion into the C-C bond - Ahire, Milind M.; Khan, Ruhima; Mhaske, Santosh B. (Organic Letters, 2017)
An efficient process for the preparation of valuable o-methyl trifluoromethyi sulfide substituted benzopheriones has been developed. The transition-metal-free method features insertion of aryne into a C-C sigma-bond under mild reaction conditions for the first time to achieve ortho-difunctionalized arenes containing a pharmaceutically important trifluoromethylthio functional group. A wide substrate, scope has been demonstrated for the developed protocol.